2021
DOI: 10.1007/s00702-021-02311-5
|View full text |Cite
|
Sign up to set email alerts
|

The role of stress coping strategies for life impairments in ADHD

Abstract: Attention-deficit/hyperactivity disorder (ADHD) is commonly accompanied by functional impairments within personal, professional, and social context as well as further psychological distress. The role of perceived stress has been examined in this regard, although little is known about the influence of stress coping strategies. We examined the dynamics between ADHD symptomatology, stress coping strategies, and life impairments in a sample of 230 clinical and non-clinical adult individuals. ADHD was associated wi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
5
0
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 11 publications
(10 citation statements)
references
References 45 publications
0
5
0
1
Order By: Relevance
“…The presence of current ADHD symptoms was assessed using the ADHD-SB questionnaire (ADHD-SB,[ 45 ], which is an instrument based on the ICD-10 research criteria and the diagnostic criteria according to DSM-IV. Since relevant information about the severity of the psychiatric impairments goes missing using categorical representations and because previous studies claimed subclinical ADHS should also be included in research [ 35 ], we chose a dimensional approach and applied the sum scores of both WURS-k and ADHD-SB to calculate the incremental predictive validity of the ADHD symptomology beyond the VRAG-R risk assessments (e.g., [ 6 ].…”
Section: Methodsmentioning
confidence: 99%
“…The presence of current ADHD symptoms was assessed using the ADHD-SB questionnaire (ADHD-SB,[ 45 ], which is an instrument based on the ICD-10 research criteria and the diagnostic criteria according to DSM-IV. Since relevant information about the severity of the psychiatric impairments goes missing using categorical representations and because previous studies claimed subclinical ADHS should also be included in research [ 35 ], we chose a dimensional approach and applied the sum scores of both WURS-k and ADHD-SB to calculate the incremental predictive validity of the ADHD symptomology beyond the VRAG-R risk assessments (e.g., [ 6 ].…”
Section: Methodsmentioning
confidence: 99%
“…In conclusion, this study has shown that ADHD symptoms are associated with higher odds for stress and that in turn, stress is an important factor in the association between ADHD symptoms and suicidal ideation. As there is some indication that individuals with ADHD/ADHD symptoms may use maladaptive coping strategies in response to stressful situations ( 63 ), some of which may be linked to increased life impairments ( 64 ), then the results of this study underscore the importance of identifying sources of stress in this population and of both developing and fostering the use of stress management techniques ( 65 ) and adaptive stress coping strategies ( 64 ).…”
Section: Discussionmentioning
confidence: 93%
“…Therefore, the changes in the magnitude of RSA with exposure to stress may provide significant information regarding an individual’s behavioral and physiological flexibility to stress (Gentzler et al, 2009; Porges, 1995). Of concern, ADHD patients are more prone for using maladaptive stress coping measures (Barra et al, 2021).…”
Section: Discussionmentioning
confidence: 99%
“…The flexibility for adaptation to stress for an individual has been found to reflect through the prompt removal of the parasympathetic brake upon presentation of cognitive stress (Gentzler et al, 2009;Schwerdtfeger, 2012). Therefore, the changes in the magnitude of RSA with exposure to stress may provide significant information regarding an individual's behavioral and physiological flexibility to stress (Gentzler et al, 2009;Porges, 1995).Of concern, ADHD patients are more prone for using maladaptive stress coping measures (Barra et al, 2021).…”
Section: Discussionmentioning
confidence: 99%